A research on the international competition ability measure of Chinese ICT industry. (2018) - Li, Hai-Chao; Fan, Shi-Jie
ICT industry is playing a key role nowadays and in the future world economic development, and has become the focus of world economic competitions. In the process of making current empirical investigation on the international competition ability of the ICT industry, we meet great difficulties. The research on the international competition ability measure of Chinese ICT industry can remedy the shortcomings of the theory research and also benefit for determining Chinese ICT status in the world, in that way we can get the access to make improvements for the international competition ability of the Chinese ICT industry. To further explore and discover the level of international competition ability of the ICT industry in a scientific way, some famous scholars choose the evaluation index on the mixing of the ICT industry's specific characteristics. In this paper, we have selected RCA index, MS index, TC index and CA index as measuring indexes and find out the weight of these indexes and time sequence through advanced entropy method to measure international competition ability of the Chinese ICT industry. The results show that the international competition ability of Chinese ICT industry is in the second place among 15 countries, with a higher level of international competition ability.